Controlling the Stochastic Sensitivity in Nonlinear Discrete-Time Systems with Incomplete Information - Lev Ryashko; Irina Bashkirtseva (Discrete Dynamics in Nature and Society)
For stochastic nonlinear discrete-time system with incomplete information, a problem of the stabilization of equilibrium is considered. Our approach uses a regulator which synthesizes the required stochastic sensitivity. Mathematically, this problem is reduced to the solution of some quadratic matrix equations. A description of attainability sets and algorithms for regulators design is given. The general results are applied to the suppression of unwanted large-amplitude oscillations around the equilibria of the stochastically forced Verhulst model with noisy observations.